1992
DOI: 10.1161/01.atv.12.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function and composition in heart transplant recipients compared with nontransplanted coronary patients.

Abstract: Accelerated coronary artery disease seems to be the main condition limiting long-term survival after heart transplantation. Ninety-one heart transplant recipients were compared with 94 nontransplanted coronary artery disease patients in an attempt to identify the factors responsible for the accelerated form of coronary artery disease occurring after heart transplantation. Among the parameters examined, heart transplant recipients exhibited a higher plasma level of insulin (8.5±0.5 versus 62±03 mIU/1, p=0.002),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 46 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Increase in serum factors inducing platelet aggregation has been seen in acute pancreatitis in dogs, and changes in platelet plasma membrane lipid composition have been suggested to increase aggregability in humans with diabetes mellitus and some cardiovascular disorders. [40][41][42] A shortened platelet life span can explain findings of platelet hyperaggregability because young platelets are more active than older platelets. 43 The high prevalence of macrothrombocytosis could indicate an increased thrombocytopoiesis in CKCS, 21 but in this study, an increased platelet aggregation was found only in CKCS with Ͼ100,000 platelets/Lwhich are not the ones that usually have macrothrombocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in serum factors inducing platelet aggregation has been seen in acute pancreatitis in dogs, and changes in platelet plasma membrane lipid composition have been suggested to increase aggregability in humans with diabetes mellitus and some cardiovascular disorders. [40][41][42] A shortened platelet life span can explain findings of platelet hyperaggregability because young platelets are more active than older platelets. 43 The high prevalence of macrothrombocytosis could indicate an increased thrombocytopoiesis in CKCS, 21 but in this study, an increased platelet aggregation was found only in CKCS with Ͼ100,000 platelets/Lwhich are not the ones that usually have macrothrombocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the accelerated form of CHD typical of the posttransplantation patient, higher levels of lipid peroxidation [53][54][55] and of oxidized LDL [56] were found compared with the stable form of CHD in the nontransplanted patients. Reactive oxygen metabolites and oxidants influence thrombus formation [57], and platelet reactivity is significantly higher in transplanted patients than in nontransplanted CHD patients [58]. However, platelet phospholipid fatty acids (which partly determine platelet function) are different from those of the nontransplanted CHD patients [58] which may explain, at least partly, the high platelet reactivity of the transplanted.…”
Section: Role Of Inflammation In Chdmentioning
confidence: 99%
“…Reactive oxygen metabolites and oxidants influence thrombus formation [57], and platelet reactivity is significantly higher in transplanted patients than in nontransplanted CHD patients [58]. However, platelet phospholipid fatty acids (which partly determine platelet function) are different from those of the nontransplanted CHD patients [58] which may explain, at least partly, the high platelet reactivity of the transplanted. As the effects of reactive oxygen metabolites on platelet function are quite complex [59], further studies are warranted to definitely answer the question of the relations between lipid peroxidation and platelet function in CHD.…”
Section: Role Of Inflammation In Chdmentioning
confidence: 99%
“…28 Since long ago, it has been demonstrated that heart transplant recipients have elevated levels of hemostatic and proinflammatory markers, mirroring the findings in non-transplant insulin resistant individuals. 29 The published data confirms that heart transplant recipients are insulin resistant, and suggests that this state of impaired insulin action accelerates CAV.…”
Section: Insulin Resistance Syndrome In the Pathophysiology Of Cavmentioning
confidence: 66%